PLANTS AS A SIGN OF LATGALIAN IDENTITY IN CULTURAL LANDSCAPE, WRITING AND STORIES - Svilāns, Andrejs; Roze, Daina; Lukaševičs, Valentīns (Via Latgalica, 2012)
Mass settlement of Latvian rural inhabitants in towns and cities started just a little more than a hundred years ago, therefore bond with nature is a specifically Latvian identity sign. Studying the peculiarities of a nation, garden and plants give an opportunity to see and understand what is hard to get in a direct way as garden reveals the hidden and open processes that have taken place and are still happening in the economic, political, and social life of an individual person or the whole society. To form a perspective on the plants existing in the cultural environment as a socially significant phenomenon in Latvian identity development and preservation, in 2008 interdisciplinary research „Plants as a sign of Latvian identity” was initiated in Latvia.The present article „Plants as a sign of Latgalian identity in cultural landscape, writing, and stories” covers the results of the fifth cycle of the above mentioned research. The goal of the research was to make out which plants are assumed to be the sign of Latgalian identity. The authors of the present paper were interested in singling out the factors that were considered essential by respondents in the formation of the notion of Latgalian plants, the colours believed to belong with Latgalian garden. Collecting stories was also considered important because not everything is preserved in written sources and, as the previous studies revealed, respondents’ stories were those that made it possible to understand the role of plants in the sustaining of identity. The research made use of questionnaire and written interview. The obtained results were analyzed by means of the comparative method using evidence of the cultural landscape, popular works by Latgalian authors, press periodicals published in Latgalian, literature in horticulture and gardening, archive materials of the Open-Air Ethnographical Museum of Latvia, internet resources, postcards from the private collection of Andrejs Svilāns and the prior results gained within the interdisciplinary research „Plants as a sign of Latvian identity”. We set to reveal in the research what opportunities for investigating Latgalian identity are offered by the plants grown in the cultural landscape of Latgale and the way the obtained results extend the existing studies of Latvian identity.Summarizing the results of 93 questionnaires and oral interviews, 139 diversities were recognized as Latgalian plants including 54 caulescent plants – decorative plants, 35 vulnerary plants and herbs, 22 trees and 28 shrubs. The notion of the Latgalian as well as Latvian plants, according to the respondents, has been formed mostly by the gardens seen by their parents, grandparents, relatives as well as their stories. The impact of fiction and classical folklore is recognized as most essential in case of Latvian plants. The plants growing in the cultural landscape used by writers of fiction are signs that are understood and unite people belonging to a particular cultural space, they function as symbols of Latgale and the native homestead. Works produced both in Latgalian and Latvian literary language by Latgalian authors have cultivated and continue to cultivate Latgalian self-awareness, but print bans and works produced before emigration and during emigration by Latgalian writers have attributed specific worth to fiction and folklore.The research revealed that identity signs are rather stable; both Latvian and Latgalian plants were most often assumed to be those grown by a couple of preceding generations – basically at the end of the 19th –beginning of the 20th century in estate and peasant gardens. These plants are considered to be Latgalian though their origin in most cases is not the local flora. At the same time in their replies to the question what should not be grown in a Latgalian garden respondents replied – „foreign plants”, meaning plants that had entered rural homesteads later on (in recent decades).The research showed that, unlike respondents from other regions, Latgalians perceive their regional landscape in a more syncretic way, not excluding plants that, due to some stereotypical notions or symbolism, do not „fit” into it, e. g. alders, asps, osiers, etc.Traditions are formed in a long-term period, but those originated in the second half of the 19th century had a special significance. Under conditions of Russification, they helped to maintain Latgalian identity, also planting particular plant combinations in line with the notion of a Latgalian garden.The information concerning plants grown in peasant homesteads in Latgale is rather scarce in the materials of the Open-Air Ethnographical Museum of Latvia, as compared to other regions. Investigation of detached homestead and village garden cultures might be a task of the further research, as village was a closed community that maintained Latvian traditions.The research brought out several debatable issues that remain unanswered. To find answers to them, a necessity to address directly the supplier of information emerged clearly in further research as well as to prepare visual material – photographs, drawings that would make it easier to identify plants and reduce the problem of taxonomic differentiation that appeared in the preceding research. For instance, it is not clear where is the border between „briar-roses” – wild rose species (Rosa sp.) and cultivated rose species and old cultivars as well as between willows (Salix fragilis), pussy willows (S. caprea or S. acutifolia x daphnoides ‘Pashal’) a. o. taxa of the genus Salix.The present paper does not pretend to provide an exhaustive study and analysis of the factors affecting the notion of the Latgalian plants. This is the task of further studies, as, according to the prior studies of Latvian plants, each such factor is worth a separate voluminous research.The authors of the present paper intend to proceed with the studies of garden culture as well as collecting the Latgalian names of plants grown at home, in the garden, growing in the forest, meadow, field, studying the use of plants and their economic and social significance as well as collecting stories in order to preserve this non-material culture legacy as complete and correct as possible. We hope that the paper will encourage researchers of various fields to participate in the study to use the opportunities provided by garden plants for a more unusual insight.